Hypoxia-Induced Mesenchymal Stem Cells Exhibit Stronger Tenogenic Differentiation Capacities and Promote Patellar Tendon Repair in Rabbits - Guanyin Chen; Wangqian Zhang; Kuo Zhang; Shuning Wang; Yuan Gao; Jintao Gu; Lei He; Weina Li; Cun Zhang; Wei Zhang; Meng Li; Qiang Hao; et al. (Hindawi Limited, 2020)
Tendon injury is a common but tough medical problem. Unsatisfactory clinical results have been reported in tendon repair using mesenchymal stem cell (MSC) therapy, creating a need for a better strategy to induce MSCs to tenogenic differentiation. This study was designed to examine the effect of hypoxia on the tenogenic differentiation of different MSCs and their tenogenic differentiation capacities under hypoxia condition in vitro and to investigate the in vivo inductility of hypoxia in tenogenesis. Adipose tissue-derived MSCs (AMSCs) and bone marrow-derived MSCs (BMSCs) were isolated and characterized. The expression of hypoxia-induced factor-1 alpha (Hif-1α) was examined to confirm the establishment of hypoxia condition. qRT-PCR, western blot, and immunofluorescence staining were used to evaluate the expression of tendon-associated marker Col-1a1, Col-3a1, Dcn, and Tnmd in AMSCs and BMSCs under hypoxia condition, compared with Tgf-β1 induction. In vivo, a patellar tendon injury model was established. Normoxic and hypoxic BMSCs were cultured and implanted. Histological, biomechanical, and transmission electron microscopy analyses were performed to assess the improved healing effect of hypoxic BMSCs on tendon injury. Our in vitro results showed that hypoxia remarkably increased the expression of Hif-1α and that hypoxia not only promoted a significant increase in tenogenic markers in both AMSCs and BMSCs compared with the normoxia group but also showed higher inductility compared with Tgf-β1. In addition, hypoxic BMSCs exhibited higher potential of tenogenic differentiation than hypoxic AMSCs. Our in vivo results demonstrated that hypoxic BMSCs possessed better histological and biomechanical properties than normoxic BMSCs, as evidenced by histological scores, patellar tendon biomechanical parameters, and the range and average of collagen fibril diameters. These findings suggested that hypoxia may be a practical and reliable strategy to induce tenogenic differentiation of BMSCs for tendon repair and could enhance the effectiveness of MSCs therapy in treating tendon injury.